The Variety Of DMS On EFL Students’ English Writing - Muthmainnah Mursidin; Ida Ilmiah Mursidin (STKIP Andi Matappa Pangkep, 2021)
This research was to find out the variety of discourse markers (DMs) used by the EFL students in English writing. This research employed a descriptive qualitative method. The respondents of this research were the second grade of EFL students; the total students were 30 students. The research data were collected by using an instrument namely writing activity. The writing consisted by argumentative text. The data were analyzed qualitatively. The first important finding from this research was about the variety of DMs used by the students, there are 30 variety of DMs used by the students English writing. Despite the fact that DMs can create a smooth talk or make the conversation more natural, the students should be able to use DMs wisely in term of fluency and coherence measured in the students’ writing. Discourse markers tell us not only about the linguistic properties of a set of frequently used expressions, and the organization of social interactions and situations in which they are used, but also about the cognitive, expressive, social, and textual competence of those who use them.